Study of the characteristics of leachate and its influence on groundwater quality near improper landfill site in Jammu City, India. (2019) - Raina, Yawar Mushtaq; Alam, Pervez; Raina, Mohd Iqbal
Increase in groundwater contamination day by day have demonstrated the need for analysis on leachate and groundwater samples due to disposal of solid waste near an improper landfill site at Jammu City. Leachate samples were analysed for all the physicochemical parameters whereas pH, electrical conductivity, total dissolved solids (TDS), BOD, COD, alkalinity, hardness, chloride, sulphate, nitrate, iron and coliform organisms were studied for groundwater samples at different locations near the landfill site using the methods recommended by APHA-AWWA-WPCF. Presence of heavy metals in leachate samples revealed that almost every type of waste is dumped at this landfill site. The most affected sampling location as a result of mixing of leachate with groundwater was the one which was nearest to the landfill site and least affected was the farthest among all. As the distance from the landfill site was increasing, contamination level of groundwater was decreasing. Ground water locations especially to the north and east of landfill site were having parameters like pH, TDS, alkalinity, hardness, chloride, sulphate and iron on higher side then the desirable limit of BIS and hence water was found to be unfit for drinking and other domestic purposes.